PESANTREN DAN UPAYA DERADIKALISASI AGAMA - Mukodi, Mukodi (WALISONGO, 2015)
The de-radicalization of Islam in Tremas Islamic boarding school was found tohave its continuing momentums from generation to generation. Through culturalpractices as: scientific culture, religious culture, social culture, and political culturethe seeds of such de-radicalization were disseminated. However, the dynamicfluctuation of extremism both transnationally and internationally became aspecific challenge. Furthermore, the massive development of Information andCommunication Technology (ICT) significantly impacted on the mindset ofTremas boarding school community. Applying qualitative approach and phenomenologicalmethod, this article revealed how the religious de-radicalization inTremas boarding school was knitted and framed in the practices of daily culture.Such practices were carried out in order to make Islamic generations may wiselybehave and act. Moreover, Islam might ocupy as it should be, namely Islam asraá¸¥matan li âl-âÄlamÄ«n, love peace, promoting love and affection, as well as nonviolence.***Deradikalisasi agama Islam di Pondok Tremas dari generasi ke generasi senantiasamenemukan momentum. Melalui praktik budaya Pondok Tremas yangmeliputi: budaya keilmuan, budaya keagamaan, budaya sosial dan budaya politikbenih-benih deradikalisasi agama Islam disemaikan. Namun demikian, pasangsurut paham ekstremisme yang berkembang di transnasional, dan internasionalmenjadi tantangan tersendiri. Apalagi masifnya perkembangan media teknologidan informatika berekses secara signifikan pada pola pikir warga Pondok Tremas.Dengan menggunakan pendekatan kualitatif, dan metode fenomenologi, artikelini menjelaskan bagaimana deradikalisasi agama di Pondok Tremas dirajut, dandibingkai dalam praktik-praktik budaya keseharian. Hal itu, dilakukan agargenerasi Islam dapat bijak dalam bersikap dan bertindak. Lebih dari itu, agaragama Islam dapat menempati area yang semestinya, yakni agama raá¸¥matan li âl-âÄlamÄ«n, tanpa kekerasan, cinta perdamaian, dan mengedepankan cinta kasih.